A study of the adequacy of Construction Industry Standard for manual calculation in Industrialised Building System (IBS) content - Mohamad Razi Ahmad Suhaimi (2019)
This study aimed to determine the adequacy of Construction Industry Standard (CIS 18:2010) formanual calculation in Industrialised Building System (IBS) content. In addition, this studyexamined the weaknesses and improvements that needed to ensure that the manual calculation of theIBS system content used by the industry is according to the current needs. Literature research,focus groups and interviews were used to collect the data. The focus group involved 43 respondentswith two series of workshop and 32 experts for validation workshop. The findings show that, thereare several requirements for the new IBS methods and these manuals need to be reviewed after 5years of use. As a result of the focus group discussion, they have proposed the addition of severalelements such as Building Modelling Information (BIM), Prefabricated Prefinished Volumetric Construction (PPVC), Prefab Bathroom Unit (PBU) and Prefab-Staircase in the new IBSsystem. In addition, there is a suggestion to reduce the factor 0.1 of IBS score for the reusableformwork system as it involves more work compared to other IBS systems. In conclusion, new elementsfor the new IBS content manual are needed to meet the construction industry standardbased and the new construction technology. In implication, the findings could be beneficial forthe industry in term of the contribution of themanual calculation for IBS content.